Evaluation of Azolla (Azolla pinnata) as a Partial Substitute in Concentrate Ration for Improving Growth Performance and Reducing Feeding Cost in Swine - Supritam Das,; Bikash Debnath,; Keviletsu Khate,; Moaakum Pongen,; Ningthoukhongjam Soranganba,; Carolina Potshangbam,; Paihem Michui,; Michelle C. Lallawmkimi,; John Joseph,; Abhijit Debnath,; A. K. Mohanty,; Param Debbarma, (Public Health, 2026)
A feeding trial was conducted during 2024–25 at KVK Dhalai Pig Breeding Farm, Tripura to study the effect of dried Azolla supplementation in the conventional concentrate ration of piglets. A total of 20 weaned piglets were randomly allocated to five treatments in a Randomized Block Design (RBD) with four replications. The treatments were graded levels of dried Azolla replacing concentrate feed on a protein-equivalent basis. The results showed a significant (P<0.05) enhancement in growth performance, feed efficiency, health status, carcass traits, and economic returns with the increasing level of Azolla supplementation. The highest final body weight (70.8 kg), total weight gain (60.5 kg) and average daily gain (224 g/day) with the lowest feed conversion ratio (2.60) were recorded by piglets fed 900 g concentrate + 76.5 g dried Azolla. There was a decrease in feed intake and an increase in protein intake, indicating improved nutrient utilization. Health parameters indicated a lesser incidence of diarrhoea and respiratory problems in the Azolla-fed groups. Economic analysis showed a marked reduction in feed cost and a higher net return (Rs.4750) and benefit-cost ratio (1.81) in piglets fed 900 g concentrate + 76.5 g dried Azolla. Carcass characteristics also improved, with higher dressing percentage, increased lean meat content, and reduced back fat thickness. It can be concluded that dried Azolla can effectively replace a part of the concentrate feed in pig diets. Supplementation at 76.5 g/pig/day was the most efficient and economical feeding strategy in farm conditions.